Stereoselective radical tandem cyclohydrostannation of optically active di-unsaturated esters of TADDOL - Gerbino, Darío César (2008)
This paper reports the results obtained in a study on the radical addition of triorganotin hydrides, R3SnH (R = Me, n-Bu, Ph; Neophyl), to four TADDOL unsaturated diesters. It was found that diese reactions lead in high yields to products of cyclohydrostannation. It was also found that whereas the addition of these hydrides to TADDOL diacrylate and TADDOL dimethacrylate leads to the expected mixtures of two and four cycloundecane diastereoisomers, respectively, the addition of triphenyltin hydride to TADDOL disubstituted acrylates yields only four out of the 16 possible stereoisomers. The observed high stereoselectivity is consistent with the radical tandem cyclohydrostannation mechanism proposed. Only in the case of the hydrostannation of TADDOL diacrylate with trimethyl- and triphenyltin hydrides could the diastereoisomers obtained in higher proportion (5a and 8a) be isolated in pure form. The subsequent reduction (lithium aluminum hydride) of macrolides 5a and 8a afforded the corresponding optically active diols 26 and 27 in high yield. Full 1H, 13C, and 119Sn NMR data are given. © 2008 American Chemical Society.